Studi Fenomenologi: Coping Stress Guru Pendamping Khusus Wanita di Sekolah Kristen Kalam Kudus Pontianak - Sitio, Desi Kristiani; Diponegoro, A.M. (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
A special education assistant (teacher's aide) is responsible for supporting the main teacher in all aspects of teaching and learning activities, from planning to evaluation. Teaching children with special needs is more complex and risky, leading to higher levels of stress compared to teaching typical children. Therefore, an effective regulatory system is needed, along with the implementation of stress coping mechanisms, to reduce these stress levels. The research objective is to understand stress coping mechanisms among female special education assistants at Kalam Kudus Christian School in Pontianak. This study employs a qualitative method with a phenomenological approach. Data collection will be conducted through interviews and observations with six female special education assistant subjects. The data collection technique used is purposive sampling, and data analysis employs content analysis. Research validity will be tested using triangulation and member checking. The research results show that the study subjects use two types of stress coping mechanisms: emotion-focused coping and problem-focused coping. The emotion-based coping results include seeking social emotional support, escape avoidance, and accepting responsibility. Additionally, the problem-based coping results include seeking informational support and confrontive coping, which influence their approach to reducing stress levels.